PENGARUH FAKTOR INTERNAL, FAKTOR EKSTERNAL DAN MATAKULIAH KEWIRAUSAHAAN TERHADAP JIWA WIRAUSAHA (Studi Pada Mahasiswa Program Studi Pendidikan Ekonomi STKIP Kie Raha Ternate) - Faisal Y Habsyi (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2021)
This study aims to determine the influence of internal factors, external factors and entrepreneurship education courses on the entrepreneurial spirit of students in the economic education study program semesters IV, VI and VIII STKIP Kie Raha Ternate who have attended entrepreneurship education courses, of the 50 students who were made respondents and distributed questionnaires. Only 47 questionnaires were analyzed. The research method used is explanatory survey with analysis techniques using multiple regression and using validity, reliability and classical assumption tests. The results showed that the Internal Factors and Entrepreneurship Education Subjects had no effect on the entrepreneurial spirit while the External Factors had a significant effect on the Entrepreneurial Spirit. Meanwhile, the F test shows that the variables of Internal Factors, External Factors and Entrepreneurial Education courses together have a significant effect on the entrepreneurial spirit.